Dissections or prosections: Which method has a better impact on sustainable gross anatomy knowledge? - Balagobi, B.; Manujasri, W.; Malith, H.; Narada, R.; Lamindu, N.; Joseph, A.; Rohan, J. (All India Institute Of Medical Sciences, 2023)
Background. Assessing the level of knowledge of anatomy of undergraduate students four years after their primary anatomy training will give a better indication as to which system of teaching is more effective. We aimed to ascertain which method was more effective at establishing a core of anatomy knowledge that could be recalled after a considerable amount of time. Methods. We tested two groups of medical students in their final year on the key concepts of gross anatomy using a question paper that included true–false type questions and identification of anatomical line diagrams. These two batches of students followed a dissection-based curriculum and a newly introduced prosections-based curriculum at the beginning of their medical education. The prosectionsbased curriculum brought with it a reduction in the in-class teaching and learning activities when compared to the old curriculum. This would in turn reflect how much anatomy knowledge one would possess when they start to practise medicine as a newly qualified doctor and also embark on a postgraduate training programme. The two groups were subjected without prior warning to a question paper that had six questions, each with five true–false statements and four questions on identification and labelling of anatomical line diagrams. Results. There was no statistically significant difference in the marks obtained for the true–false type questions between the two groups (p=0.08), but the prosections group obtained higher marks for the diagram identification questions (p=0.02). Conclusion. A prosection-based curriculum when compared to a dissection-based curriculum was equally effective at establishing a core of gross anatomy knowledge.